2019
DOI: 10.32014/2019.2518-170x.68
|View full text |Cite
|
Sign up to set email alerts
|

Approbation of PCR-RFLP and as-PCR Methods for Genotyping Cattle by the Dgat1 Gene

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A lot of data was obtained in studies of thermostability and cheese aptitude of milk from cows with different genotypes by milk proteins such as alfa S1-casein (CSNISI), beta-casein (CSN2), kappa-casein (CSN3) and beta-lactoglobulin (BLG). On the basis of genotyping of the black-multicolored and Holstein cows according to CSN3 gene by the PCR-RFLP method of analysis, it was shown that milk from cows with BB genotype CSN3 possessed reduced thermostability (39,3±5,43 min), AA genotype -increased thermostability (57.2±1,61 min) and milk of the animals with AB genotype took the intermediate position (56.5±2.52 min) [15,16,17].…”
mentioning
confidence: 99%
“…A lot of data was obtained in studies of thermostability and cheese aptitude of milk from cows with different genotypes by milk proteins such as alfa S1-casein (CSNISI), beta-casein (CSN2), kappa-casein (CSN3) and beta-lactoglobulin (BLG). On the basis of genotyping of the black-multicolored and Holstein cows according to CSN3 gene by the PCR-RFLP method of analysis, it was shown that milk from cows with BB genotype CSN3 possessed reduced thermostability (39,3±5,43 min), AA genotype -increased thermostability (57.2±1,61 min) and milk of the animals with AB genotype took the intermediate position (56.5±2.52 min) [15,16,17].…”
mentioning
confidence: 99%
“…On the other hand, in view of the limited amount of high-quality raw milk and the seasonality of its production, the possibility of producing DWM, for example, from non-heat-resistant raw materials, the quality of which can be improved by using food additives, is excluded. In this situation, the DWM production with use of salts is permissible to carry out under technical conditions or standards of organizations [2,4,[19][20][21].…”
mentioning
confidence: 99%